Isradipine – a calcium channel blocker – does not potentiate chloroquine antiplasmodial activity against Plasmodium falciparum - Randrianarivelojosia M.; Jambou R. (Parasite, 2005)
Culturing fresh clinical isolates of P. falciparum and using the isotopic method, we tested separately chloroquine and isradipine – a calcium channel blocker –, and also the combination isradipine plus chloroquine. Tested wild isolates were chloroquinesensitive. With regard to the combination isradipine/chloroquine, the isobolograms obtained indicate that isradipine antagonises chloroquine antiplasmodial activity. Taking into account these findings, we discuss the issues related to the calcium channel blocker molecules.